Hubungan Distres Emosional dan Dukungan Sosial dengan Kualitas Hidup Lansia Penderita Diabetes Melitus di Kabupaten Sleman - Reka Septiara Irawati; Heru Subekti (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2022)
Background: Diabetes mellitus is one of the degenerative illnesses in elderly caused by inadequate production of insulin. Diabetes mellitus need a long-term management which can lead to emotional distress and diminishing life quality. Social support is playing an important role toward diabetic management and distress coping. Diabetics patient needs social support to lower emotional distress and improve quality of life.Objective: To determine the correlation between emotional distress, social support with quality of life among elderly patients with Diabetes Mellitus in Sleman Regency.Method: This was a correlational study using cross sectional design. Subjects were 188 elderlies with Diabetes Mellitus in Sleman Regency, selected by purposive sampling method. Data were collected using questionnaire of Problem Area in Diabetic, social support (by Kim, Shimada, Sakano), and WHO Quality of Life-BREF (WHOQOL-Bref). Data was analysed using Spearman correlation.Results: The Spearman Rank analysis result for emotional distress and quality of life variables is r=-0,289, p=0,000; and r=0,230, p=0,002 for social support and quality of life variables. While for social support and emotional distress variables the result is r=0,038, p=0,605.Conclusion:  There is significant negative correlation between emotional distress and quality of life among elderly with DM; while there is positive significant correlation between social support and quality of life. However, there is no significant correlation between social support and emotional distress among elderly with DM in Sleman regency. Therefore, it was necessary to pay attention to the psychosocial aspects in providing nursing care for type 2 diabetes patient.ABSTRAKLatar Belakang: Diabetes melitus merupakan penyakit degeneratif pada lansia karena produksi insulin yang tidak adekuat. Diabetes melitus membutuhkan manajemen jangka panjang sehingga penderitanya berisiko mengalami distres emosional dan menurunkan kualitas hidup. Dukungan sosial penting dalam manajemen diabates dan koping distres emosional. Penderita diabetes melitus memerlukan dukungan sosial untuk menurunkan distres emosional dan meningkatkan kualitas hidup.Tujuan: Untuk mengetahui hubungan distres emosional dan dukungan sosial dengan kualitas hidup lansia penderita diabetes melitus di Kabupaten Sleman.Metode:Penelitian correlational menggunakan rancangan cross sectional pada 188 responden lansia penderita DM di Kabupaten Sleman yang dipilih dengan metode purposive sampling. Data penelitian diperoleh menggunakan kuesioner Problem Area in Diabetic (PAID); Dukungan Sosial oleh Kim, Shimada dan Sakano; dan WHO Quality of Life-BREF (WHOQOL-Bref). Analisis data menggunakan uji Spearman correlation.Hasil: Hasil analisis Spearman untuk variabel distres emosional dan kualitas hidup didapatkan nilai r=-0,289, p=0,000; dan r=0,230, p=0,002 untuk variabel dukungan sosial dan kualitas hidup. Sementara untuk variabel diukungan sosial dengan distres emosional nilai r=0,038, p=0,605.Kesimpulan: Terdapat hubungan yang signifikan antara distres emosional dengan kualitas hidup lansia dengan DM dengan arah negatif. Sementara ada hubungan yang signifikan dengan arah positif antara dukungan sosial dengan kualitas hidup lansia dengan DM. Namun, tidak ada hubungan yang signifikan antara distres emosional dan dukungan sosial pada lansia dengan DM di Kab Sleman. Oleh karena itu perlu diperhatikan aspek psikososial dalam memberikan asuhan keperawatan pada penderita DM tipe 2.